Are Financial Ratios Able to Predict Bank Stock Prices During the COVID-19 Pandemic? - Kristiono, Archangela Valerie (Owner : Riset dan Jurnal Akuntansi, 2024)
Fundamental analysis, such as financial ratios, is important to ensure capital markets move efficiently. This analysis represents 69% of the variation in stock prices in the capital market. However, fundamental analysis has not been widely carried out because expertise is needed to analyze qualitative and quantitative data from company characteristics that underlie the movement of a stock. In 2020 – 2022, bank performance experienced fluctuations due to the Covid-19 pandemic which caused bank share prices to also fluctuate. On the other hand, banks have an important role as intermediary institutions or intermediaries to support the funding needs of the real sector or the business world. However, previous research on fundamental analysis largely excluded companies in the financial sector. Therefore, this article aims to find out whether financial ratios are able to predict bank share prices during the Covid-19 pandemic. There are five financial ratios used in this research, namely loan loss provision ratio, total capital ratio, profit margin ratio, current ratio, and solvency ratio. The population in this study are financial companies listed on the Indonesia Stock Exchange for the period 2020 - 2022. The sample was selected using a purposive sampling method and obtained 38 companies and 114 observations. The results of multiple regression analysis show that the loan loss provision ratio has a significant negative effect and the total capital ratio has a significant positive effect on bank share prices. Meanwhile, the net profit margin ratio, current ratio and solvency ratio do not have a significant effect on bank share prices. This research has implications for encouraging banks to improve disclosure policies and encouraging investors to hone fundamental analysis skills to reduce mispricing and make markets more efficient.